Avaliação de fibras de gravatá, macaúba e curauá para aplicação em compósitos de polipropileno obtidos por mistura termocinética - Simão, José Alexandre (2018)
The objective of this project was the study of polypropylene and natural fibers high filled composite panels, with and without coupling agents, and the extraction and study of three species of natural fibers as potential reinforcements: macaúba (Acrocomia aculeata) , fibers of the leaves of gravatá (Bromelia balansae) and fibers of the leaves of curauá (Ananas erectifolius). Their characterizations indicated the fibers of the gravate sheets with the greatest potential for reinforcement of the panels studied, presenting a 40 GPa elastic modulus, a crystallinity index of 58% and a thermal degradation start temperature around 244°C. Strategies of processing were used to determine the concentration of the coupling agents (5% (w/w) of PPMA and SEBS-MA) and the pressure of the molding of the panels. However, with the use of PPMA, there was a 150% increase in flexural strength and the presence of SEBS-MA increased by 150% the impact strength of the composites with 80% fiber, the value obtained being 40 J/m. The presence of high fiber fractions in the composites decreased the thermal resistance of the composites, determined by thermogravimetric analysis, by 10°C. The results of DSC and DMTA showed that the high fiber contents of gravatá restricted the mobility of the PP chains, reducing the crystallinity of the PP and shifting the Tg to larger values. The composites absorbed about 4.5% moisture and the values are lower when compared to commercial panels such as MDF and HDF. The work demonstrated the potential of high filled composite with gravata fibers obtained through thermokinetic mixing and hot compression molding.